Small Airway Dysfunction Measured by Impulse Oscillometry and Fractional Exhaled Nitric Oxide Is Associated With Asthma Control in Children - Lin, Liang-Mei; Chang, Yu-Jun; Yang, Kuender D.; Lin, Ching-Hsiung; Chien, Jien-Wen; Kao, Jun-Kai; Lee, Ming-Sheng; Chiang, Tsay-I; Lin, Ching-Yuang; Tsai, Yi-Giien (Frontiers in Pediatrics, 2022)
Background Impulse oscillometry (IOS) and fractional exhaled nitric oxide (FeNO) are sensitive and non-invasive methods to measure airway resistance and inflammation, although there are limited population-based studies using IOS and FeNO to predict asthma control. Objective This study aimed to investigate the utility of IOS and FeNO for assessing childhood asthma control in terms of small airway dysfunction and airway inflammation. Methods This prospective observational cohort study enrolled 5,018 school children (aged 6–12 years), including 560 asthmatic children and 140 normal participants. FeNO, spirometry, IOS, bronchial dilation test, total IgE, and childhood asthma control test (C-ACT) were measured. FeNO, IOS, spirometry, and C-ACT results were correlated with childhood asthma with and without control. Results Uncontrolled asthmatic children had abnormal FeNO, IOS, and spirometric values compared with control subjects (P < 0.05). IOS parameters with R5, R5-R20, X5, Ax, △R5, and FeNO can predict lower C-ACT scales by the areas under receiver operating characteristic curves (AUCs) (0.616, 0.625, 0.609, 0.622, 0.625, and 0.714). A combination of FeNO (>20 ppb) with IOS measure significantly increased the specificity for predicting uncontrolled asthma patients compared with FeNO alone (P < 0.01). A multiple regression model showed that small airway parameter (R5-R20) was the strongest risk factor [OR (95% CI): 87.26 (7.67–993.31)] for uncontrolled asthma patients. Poor control with lower C-ACT scales correlated with high FeNO (r = −0.394), R5 (r = −0.106), and R5-R20 (r = −0.129) in asthmatic children (P < 0.05). Conclusion A combined use of FeNO and IOS measurements strongly predicts childhood asthma with or without control.